Mobile Advertising, Product Social Value dan Purchase Intention pada Instagram - Ni Wayan Sinta Wahyuni; Gede Sri Darma (Universitas Pendidikan Nasional, 2019)
ABSTRACTThe purpose of this study is to find out and analyze the influence of attitude towards mobile advertising and moral value on purchase intention, and to find out the mediating role of attitudes towards mobile advertising to the effect of social value on the purchase intention of instagram application users. The population used in this study were all residents of the Bali island, at least have graduated from high school, and become active users of Instagram social media and are aware of the sponsored ads feature on Instagram, whose numbers cannot be calculated definitively (infinite). Data collection was done by using the questionnaire method. The analysis technique used was partial least square (PLS). The results showed that social value has a positive and significant effect on attitudes towards mobile advertising, social value and attitude towards mobile advertising has a positive and significant effect on purchase intention, and attitude towards mobile advertising can mediate the influence of social value on purchase intention. This research is expected to be a reference and consideration for company management to be able to increase the purchase intention of the consumers by utilizing mobile advertising through social media applications, by paying attention to consumer attitudes and the influence of social values on these mobile advertisements.